Identifying key factors for predicting the age at peak height velocity in preadolescent team sports athletes using explainable machine learning - Retzepis, N.-O.; Avloniti, A.; Kokkotis, C.; Protopapa, M.; Stampoulis, T.; Gkachtsou, A.; Pantazis, D.; Balampanos, D.; Smilios, I.; Chatzinikolaou, A. (Sports, 2024)
Maturation is a key factor in sports participation and often determines the young athletes` characterization as a talent. However, there is no evidence of practical models for understanding the factors that discriminate children according to maturity. Hence, this study aims to deepen the understanding of the factors that affect maturity in 11-year-old Team Sports Athletes by utilizing explainable artificial intelligence (XAI) models. We utilized three established machine learning (ML) classifiers and applied the Sequential Forward Feature Selection (SFFS) algorithm to each. In this binary classification task, the logistic regression (LR) classifier achieved a top accuracy of 96.67% using the seven most informative factors (Sitting Height, Father`s Height, Body Fat, Weight, Height, Left and Right-Hand Grip Strength). The SHapley Additive exPlanations (SHAP) model was instrumental in identifying the contribution of each factor, offering key insights into variable importance. Independent sample t-tests on these selected factors confirmed their significance in distinguishing between the two classes. By providing detailed and personalized insights into child development, this integration has the potential to enhance the effectiveness of maturation prediction significantly. These advancements could lead to a transformative approach in young athletes` pediatric growth analysis, fostering better sports performance and developmental outcomes for children.